Mass spectrometry-based multi-attribute method in protein therapeutics product quality monitoring and quality control. Issue 1 (31st December 2023) - Yang, Feng; Zhang, Jennifer; Buettner, Alexander; Vosika, Eva; Sadek, Monica; Hao, Zhiqi; Reusch, Dietmar; Koenig, Maximiliane; Chan, Wayman; Bathke, Anja; Pallat, Hilary; Lundin, Victor; et al.
ABSTRACT: The multi-attribute method (MAM), a liquid chromatography-mass spectrometry (LC-MS)-based peptide mapping method, has gained increased interest and applications in the biopharmaceutical industry. MAM can, in one method, provide targeted quantitation of multiple site-specific product quality attributes, as well as new peak detection. In this review, we focus on the scientific and regulatory considerations of using MAM in product quality attribute monitoring and quality control (QC) of therapeutic proteins. We highlight MAM implementation challenges and solutions with several case studies, and provide our perspective on the opportunities to use MS in QC for applications other than standard peptide mapping-based MAM.